1999
DOI: 10.1007/bf03395309
|View full text |Cite
|
Sign up to set email alerts
|

Errors and Response Latencies as a Function of Nodal Distance in 5-Member Equivalence Classes

Abstract: Two experiments were conducted to investigate the relationship between nodal distance, response accuracy, and response latency during testing for emergent relations. In both experiments, undergraduate subjects first learned A-B, B-C, C-D, and D-E constituent relations of six 5-member equivalence classes. In Experiment 1, only selected tests of trained and of 0-, 1-, and 2-node tests of emergent relations were carried out in order to avoid testing of 0-or 1-node relations that might form constituents of the 2-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 19 publications
4
48
1
1
Order By: Relevance
“…The reaction time was longer with an increased number of nodes, that is, the reaction time was longer in the LS training structure with 4 members than with 3-members. This is in accordance with previous research (Arntzen & Holth, 2000b;Bentall, et al, 1999;Fields, Adams, Newman, & verhave, 1990), but not in accordance with Imam (2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reaction time was longer with an increased number of nodes, that is, the reaction time was longer in the LS training structure with 4 members than with 3-members. This is in accordance with previous research (Arntzen & Holth, 2000b;Bentall, et al, 1999;Fields, Adams, Newman, & verhave, 1990), but not in accordance with Imam (2006).…”
Section: Discussionsupporting
confidence: 91%
“…However, the effects of the number of nodes can only be studied when using a linear series training structure, because increasing the number of members in each class does not influence the number of nodes in MTO or OTM. A number of studies have found nodal effects, i.e., stimulus equivalence outcome decrease and reaction time increase, to be a function of the number of nodes (e.g., Arntzen & Holth, 2000b;Bentall, Jones, & Dickins, 1999;Fields, Landon-Jimenez, Buffington, & Adams, 1995;Kennedy, 1991). On the other hand, some other findings contradict this when the number of trials is equal per nodal number (Imam, 2006).…”
mentioning
confidence: 99%
“…Se, por exemplo, os compostos em um treino discriminativo com discriminações simples fossem formados por três elementos, em vez de dois como tem sido feito (e.g., A1B1C1) e, após os treinos, fossem conduzidos os testes AB, BA, A-B, B-A, BC, CB, B-C, C-B, AC, CA, A-C e CA, poder-se-ia falar Alguns autores têm proposto que a latência de resposta (ou tempo de reação) pode funcionar como uma medida indireta da formação de classes de equivalência (e.g., Spencer & Chase, 1996). No presente estudo, as latências de resposta ao estímulo de escolha/comparação foram registradas e alguns padrões encontrados, nos dois estudos, replicaram estudos anteriores (e.g., Bentall et al, 1998;Spencer, & Chase, 1996): (1) latências semelhantes para as relações de cada classe de equivalência; (2) latências maiores para as relações de transitividade e equivalência.…”
Section: Discussão Geralunclassified
“…In addition, it has been reported that comparison response latencies increase from directly taught baseline trials to derived symmetry, transitivity, and equivalence probe trials (Bentall, Dickins, & Fox, 1993;Spencer & Chase, 1996;Wulfert & Hayes, 1988), and when tests for emergent relations involve increasing numbers of nodes (Bentall, Jones, & Dickins, 1998;Fields, Adams, Verhave, & Newman, 1990;Fields, Landon-Jimenez, Buffington, & Adams, 1995;Imam, 2001;Kennedy, 1991;Kennedy, Itkonen, & Lindquist, 1994;Spencer & Chase, 1996). This positive relation between latencies and nodal number also has suggested to some that the formation of equivalence relations involves verbal mediating behavior in the form of stimulus names (e.g., or problem-solving strategies (e.g., .…”
Section: ____________________________________________________________mentioning
confidence: 99%